EVOLVING ROLE OF THE JUDICIARY IN THE CONTEXT OF NEW TECHNOLOGIES AND EMERGING CHALLENGES (International Journal of Food and Nutritional Sciences, 2022)
The judiciary should decipher current laws considering emerging technologies to answer new legitimate issues. Judges need to work out some kind of harmony between the complexities of state of the art innovation like blockchain and man-made consciousness and laid out legitimate statutes. This calls for close assessment of earlier lawful choices, a modern handle of innovation improvements, and a devotion to saving legitimate consistency and consistency. To determine uncertainty and vagueness in the law, passes judgment on should go through their legal judgment and keep with the latest specialized progressions. Each case utilizing new technologies has its own arrangement of hardships, and court decisions might lay out huge rules for comparable cases from here on out. The judiciary can safeguard the rule of law and safeguard individual privileges in the computerized time by adjusting legitimate understanding to mirror the truth of mechanical headway.